Metabolic and Nutritional Effects of Two Types of Meals with Modified Texture in Feeding Dysphagic Subjects (P01-003-19). (13th June 2019) - Gregori, Dario; Sukkar, Samir Giuseppe; Diurni, Mario; Formenti, Laura; French, Megan; Carraro, Alice
Abstract: Objectives: Long-term hospice dysphagic patients are at risk of malnutrition, often not wanting to consume meals. Difficulties in preparing meals for these patients can include variability in manually prepared recipes, the need for varied and appetizing menus and dishes, and time restrictions for administering food. This study investigated two feeding models, (i) smoothed dishes prepared traditionally in a kitchen (CF), and (ii) meals obtained from dehydrated and rehydrated preparations by means of special equipment (OI). Methods: The study is an observational cohort of 30 patients aged between 51–81 years old with complex disability, intellectual disabilities, dysmorphism and medium-gravity dysphagia, and psychiatric, neurological, gastroenterological and endocrine comorbidities. Fifteen patients were fed the OI menu, and 15 were fed the CF menu. Follow-up was assessed at 2- and -4 months. Changes in anthropometric parameters and in nutritional status were assessed. Results: BCI phase angle was significantly lower in patients with OI than in CF subjects. Patients differed also in terms of body composition, showing a BCI significantly lower with lean and fat mass in the OI group. In addition, body water was significantly higher in the CF group. Conclusions: The instantaneous homogenized feeding method produces a substantial improvement in nutritional status in comparison to traditional smoothed meals, especially with regards to protein framework and phase angle in OI. Funding Sources: ZETA RESEARCH S.r.l.